2005
DOI: 10.1175/jtech1768.1
|View full text |Cite
|
Sign up to set email alerts
|

Stratocumulus Liquid Water Content from Dual-Wavelength Radar

Abstract: A technique is described to retrieve stratocumulus liquid water content (LWC) using the differential attenuation measured by vertically pointing radars at 35 GHz and 94 GHz. Millimeter-wave attenuation is proportional to LWC and increases with frequency, so LWC can be derived without the need to make any assumptions on the nature of the droplet size distribution. There is also no need for the radars to be well calibrated. A significant advantage over many radar techniques in stratocumulus is that the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 22 publications
1
110
0
1
Order By: Relevance
“…The IPT then applies different Z-LWC relationships depending on the precipitation conditions in the cloud, though LWC uncertainties can nevertheless be larger 50 % and the retrieval of cloud droplet size is not possible in the presence of precipitation. Hogan et al (2005) proposed the use of dual-wavelength reflectivity (DWR) methods to profile liquid water clouds. In this case the accuracy is limited by the relatively small amount of dual-wavelength attenuation obtained when using frequencies at 35 and 94 GHz (the differential mass attenuation coefficient is roughly 4 dB km −1 per g m −3 ), which can be difficult to measure and usually requires significant averaging.…”
Section: Boundary Layer Cloudsmentioning
confidence: 99%
See 3 more Smart Citations
“…The IPT then applies different Z-LWC relationships depending on the precipitation conditions in the cloud, though LWC uncertainties can nevertheless be larger 50 % and the retrieval of cloud droplet size is not possible in the presence of precipitation. Hogan et al (2005) proposed the use of dual-wavelength reflectivity (DWR) methods to profile liquid water clouds. In this case the accuracy is limited by the relatively small amount of dual-wavelength attenuation obtained when using frequencies at 35 and 94 GHz (the differential mass attenuation coefficient is roughly 4 dB km −1 per g m −3 ), which can be difficult to measure and usually requires significant averaging.…”
Section: Boundary Layer Cloudsmentioning
confidence: 99%
“…potential complete attenuation of the radar signal in rain after a few kilometres) it can also be exploited to provide water content profiles by using dual-frequency approaches. Hogan et al (2005) demonstrated water content profiling capabilities at a vertical resolution of 150 m for stratocumulus clouds with an accuracy of 0.04 g m −3 by employing the 35-94 GHz (8.6-3.2 mm) pair (when dwelling times longer than one minute are adopted). G band frequencies have the advantage of producing even larger dual-wavelength attenuation, with the possibility of more accurate profiling and of targeting thinner boundary layer clouds.…”
Section: Hydrometeor Attenuationmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, active remote sensing techniques like cloud radar (Frisch et al, 1995;Hogan et al, 2005) with rapid scanning capability provide a less direct measurement of cloud LWC (since LWC is proportional to the third moment of cloud drop size distribution but radar reflectivity is proportional to the sixth moment) and also would likely be much more costly than passive methods.…”
Section: Huang Et Al: Part 2: Observation System Simulation Expermentioning
confidence: 99%